Mitchell-Riley Syndrome Due to a Novel Mutation in RFX6 - Kambal, Mohammed Abdulmageed; Al-Harbi, Doha Ayed; Al-Sunaid, Areej Rashed; Al-Atawi, Mohsen Suliaman (Frontiers in Pediatrics, 2019)
Abstract We report a Saudi girl who presented at birth with neonatal diabetes, duodenal atresia, and progressive cholestasis. After other gene testing was negative, the clinical diagnosis of Mitchell-Riley syndrome was ultimately considered and further genetic analysis revealed a novel missense homozygous variant in RFX6: c.983A>T (p.asp328Val). Despite intensive management, the patient died from severe Klebsiella pneumoniae sepsis at 5 months of age. This rare syndrome should be suspected in any neonate with hyperglycemia complicated by intestinal atresia and/or progressive cholestasis that could suggest biliary hypoplasia. Early recognition and diagnosis through genetic testing are essential for guiding aggressive clinical management as well as family counseling, particularly in light of the high possibility of early death in this highly complex disorder.